Ritos terapêuticos : uma abordagem do sofrimento à resiliência na terapia familiar - Silva, Ana Neri Nascimento da (2007)
The dissertation analyses the use of therapeutic rites in systemic family therapy, promoting resilience in situations of suffering and crises. The first part approaches these rites from an anthropologic and psychosocial perspective, focusing in the finality of the rites in mankind as a process of recognition and insertion of the human being in the social cycle. Likewise, it approaches family rites; its functions and how the myths built in the family environment influence the appearance of suffering. Moreover, it is presented the systemic family therapy, in order to understand the use of therapeutic rites as a technique used in therapy, mainly to make a change possible in the therapeutic system. Family therapy contributes with the studies of the family vital cycle, helping to be aware of and to identify the development stages, in order to restore bonds, ruptures and stops, which cause the appearance of symptoms in the family. The second part analyses family resilience, trying to understand how some people, besides suffering enormous adversities and traumas, find power to beat the crises, ending stronger than they were before. In order to comprehend in which context the therapeutic rites are applied, this part also presents to us who is the systemic family therapist, his/her beliefs, his/her convictions, his/her personal and professional universe. The third part presents the research performed with family therapists, where their procedures with rites in therapy were investigated as well as the objective, evaluation and analysis of the therapeutic results. It was analyzed in which stages of the vital cycle more therapeutic intervention is needed with the help of the rites, assisting the family to pass the crystallized stage, providing the experience of a rite of passage. It ends with the analyses of the rites studied from an anthropologic perspective, including the three stages of a rite: margin, dissociation and aggregation. The rites are essential in the development of the human being. By these, society reaffirms its values, beliefs and identity, offering an opportunity to the individual and the collective to express them.